The Change of Diagnosis from Panic Disorder to Generalized Anxiety Disorder in the Elderly - Eksalanti Aulia Nashira; Hafid Algristian; Tutik Nur Kasiani (Sinergi International Journal of Psychology, 2026)
Anxiety disorders are common in older adults and often present with evolving clinical patterns that complicate diagnosis and management. This study aims to describe the diagnostic transition from panic disorder to generalized anxiety disorder in an elderly patient through a narrative literature review integrated with a single-case illustration. The literature was identified from major academic databases and synthesized narratively, while the clinical case involved a 62-year-old male with a history of panic disorder whose symptoms gradually shifted into persistent and generalized anxiety over a seven-year period. Clinical evaluation was supported by the Depression Anxiety Stress Scale-21 and the World Health Organization Quality of Life–BREF. The findings indicate predominant generalized anxiety symptoms with moderate impairment in quality of life and no clinically significant depressive features, possibly related to sustained pharmacological management and cumulative psychosocial and medical stressors. This case illustrates that anxiety disorders in later life may evolve dynamically over time and highlights the importance of longitudinal assessment, careful diagnostic reconsideration, and integrated biopsychosocial management. Further studies using larger samples and objective biomarkers are needed to clarify the mechanisms underlying diagnostic evolution in geriatric populations.